2011
DOI: 10.1159/000332825
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lymph Node Metastatic Pattern according to the Depth of In-Growth in the Muscularis Propria in T2 Rectal Cancer for Lateral Lymph Node Dissection

Abstract: Background/Aims: The biological behavior of rectal cancers that invade the muscularis propria (pT2) has not been well studied. We retrospectively studied the pattern of lymph node metastases in patients with T2 rectal cancer. Methods: We enrolled 88 patients who had undergone curative resection of T2 colorectal cancer through mesorectal excision and lateral pelvic lymph node dissection; we microscopically estimated the maximum depth of muscularis propria invasion and classified the results into 3 groups repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…in Japan, lateral lymph node dissection is generally indicated if the lower margin of the primary cancer is located below the peritoneal reflection or anal canal with invasion into the muscularis propria or beyond. 8 there were no cancer cells in the circumferential margin of resection in any of the cases.…”
Section: Methodsmentioning
confidence: 68%
“…in Japan, lateral lymph node dissection is generally indicated if the lower margin of the primary cancer is located below the peritoneal reflection or anal canal with invasion into the muscularis propria or beyond. 8 there were no cancer cells in the circumferential margin of resection in any of the cases.…”
Section: Methodsmentioning
confidence: 68%
“…Only 40% of our patients with cT2 CRC were confirmed as pT2 postoperatively, thus, it is still difficult for surgeons to reliably assess degrees of tumor penetration before surgery. Although endoscopic ultrasonography may help in this regard (16,17), the necessity of endoscopic ultrasonography for every patient and its broad clinical acceptance remains to be seen. Another issue is the single-center, retrospective nature of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment strategy or different concept for lateral lymph nodes may affect the local recurrence and prognosis of RC patients. Recent reports suggested that lateral lymph node dissection decreased the local recurrence and had prognostic benefits 16,17) . However, even in RC patients with lateral lymph node metastasis, some patients had a good prognosis and others had a poorer one.…”
Section: Introductionmentioning
confidence: 99%